Development of website-based teaching materials on the solar system for class V elementary school students - Aditia Wiguna, Frans; Wenda, Dhian Dwi Nur; Selan, Detika Amelia (Universitas Nusantara PGRI Kediri, 2024)
The aim of this research is to develop website-based teaching materials on the solar system for fifth grade elementary school students. This teaching material was developed as a learning resource in elementary science learning which was developed systematically and logically. The method in this research uses R&D by adapting the ADDIE development model with stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The location of this research was carried out at Emmaus Elementary School, Kediri Regency with a total of 25 test subjects. The data used to see the feasibility of the product that has been developed is product validity data, product practicality data, and product effectiveness data. The results of product validity tests carried out by material experts obtained an average value of 85%, while the validity results by design experts were 83%. The average product validity test result is 84% with valid criteria. The level of practicality and effectiveness of the teaching materials was carried out through extensive trials with the product practicality level obtaining an average score of 96% in the very practical category. Meanwhile, the results of the product effectiveness test can be seen from the comparison of the average value of classical student learning outcomes, namely 80 with a KKM of 75. Based on the comparison results, the average classical student learning outcomes are higher than the predetermined KKM, so the product can be declared effective for use in teaching. solar system material for fifth grade elementary school students.